Meningkatkan Daya Saing UMKM melalui Inovasi dan Digitalisasi pada UMKM Jaringan Wirausaha (Jawara) di Wilayah Bojongsari Depok - Sunarto, Ading; Napisah, Napisah; Putri, Aldila Rahma; Anggraini, Anggun (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic growth and community welfare. However, challenges in market competition, changing consumer behavior, and technological advancements require MSMEs to adapt through innovation and digitalization. This study aims to enhance the competitiveness of Jaringan Wirausaha (JAWARA) MSMEs in Bojongsari, Depok, by implementing innovative strategies based on digital technology. The Program Kreativitas Mahasiswa (PKM) methodology includes SWOT analysis to identify MSMEs’ strengths and weaknesses, digital business training, and the application of product and marketing innovation strategies. Findings indicate that the adoption of digital technology, such as e-commerce, social media marketing, and customer management systems, significantly improves operational efficiency, market reach, and revenue generation for JAWARA MSMEs. This program concludes that digitalization and innovation are essential factors in enhancing MSME competitiveness in the digital economy era. With proper education, business mentoring, and technology optimization, MSMEs can grow sustainably and remain competitive. This study provides strategic recommendations for local MSMEs to leverage technology-driven innovation for sustainable economic growth.